Microbial glucosidation of 1,2,4-trihydroxy-9,10-anthraquinone (purpurin) - Steinerová, N; Matĕjů, J; Cudlín, J; Vanĕk, Z (Folia microbiologica, 1984)
Streptomyces aureofaciens glucosidizes 1,2,4-trihydroxy-9,10-anthraquinone (purpurin) added to the cultivation medium to yield the corresponding 2-beta-D-glucoside. The identity of the glucoside was demonstrated by comparing its physico-chemical properties with data of an authentic sample prepared synthetically. A further chemical glucosidation of the acetylated 2-beta-D-glucoside gives rise to 2-(hepta-O-acetyl-beta-gentiobiosyl)-4-(tetra-O-acetyl-beta-D-gluc opyranosyl) purpurin. All the derivatives are immunoactive.
Keywords: Chemical Phenomena; glukosidy; Glucosides; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; Spectrophotometry, Infrared; Streptomyces aureofaciens; Mass Spectrometry; chemické jevy; Chemistry; Anthraquinones; lektiny; Lectins; fermentace; anthrachinony; Fermentation; spektrofotometrie infračervená; hmotnostní spektrometrie; chemie